Experiência e vivência educacional no contexto das tecnologias: o Colégio dos Jesuítas durante a pandemia - Batista, Ângela Bigonha Bovarêto (Universidade do Vale do Rio dos Sinos, 2021)
The main objective of this study is to analyze the educational possibilities and challenges identified by teachers during the period of physical isolation, with regard to the incorporation of digital technologies (DT) in their pedagogical practices, aiming to support Colégio dos Jesuítas in the city of Juiz de Fora, Minas Gerais, to (re)thinking teaching training practices that can contribute to more meaningful learning. Considering knowing the perceptions of teachers about the use of Digital Technologies in education and which digital technologies that are being used by them in their pedagogical practices; understanding the limits and challenges faced by teachers in the use of digital technologies; analyzing the possibilities evidenced by teachers when incorporating technological resources in their pedagogical practices, in order to offer subsidies so that managers can propose teaching training practices that favor the use of technologies in pedagogical practices. This research is qualitative in nature. Data collection is composed of two research strategies: questionnaire and group discussion. This research had the participation of eighteen professors. The results show the use of several digital technologies used by teachers in their pedagogical practices and their perceptions about their use as a pedagogical resource, some of which are most cited such as Moodle, Microsoft Teams, Power Point and YouTube. It was also highlighted the need for training courses that work with specific tools, in an objective manner, for specific purposes, always with a view to optimize time. It was understood that the limits and challenges faced by teachers, in the use of DTs, were mainly related to the short period of time in which it was necessary to adapt to this new reality, as it required a great effort, especially with regard to the domain of digital skills and the redefinition of pedagogical practices. The educational possibilities and strategies evidenced by the teachers when incorporating technological resources in their pedagogical practice were characterized by the use of many strategies that help to motivate students and streamline remote classes. The results present teacher education as an essential element in the construction of a digital culture, these elements support the intervention proposal that proposes actions that promote the tecnologic innovation at Colégio dos Jesuítas, considering the technical (infrastructure and digital resources) and human dimensions (skills and competences).
Keywords: Tecnologias digitais; Formação de professores; Pandemia; Ensino remoto; Digital technology; Teacher training; Pandemic; Remote learning; ACCNPQ::Ciências Humanas::Educação